Ibu Soed’s “Hai Becak” Lyrics and Tone Analysis (An Ethnomusicology Research) - Melsya Firtikasari (Universitas Pasundan, 2022)
The background of the writing of this journal is to find out whether the lyrics and songs of Hai Becak from the work of SARIDJAH NIUNG BINTANG SOEDIBJO (IBU SOED) are in accordance with the criteria for the voices of children aged 4-6 years as seen from the structure of the song, melody and range of children's voices. In this research, the writer uses descriptive analysis method by collecting qualitative data by using appropriate research instrument. The various data are classified, validated, and interpreted. The result of this research is that, after the author has researched more deeply, the song by SARIDJAH NIUNG BINTANG SOEDIBJO (IBU SOED) can make a contribution, in every poem he creates a lot of education that can be given to children, be it education. divinity and social education, as well as for the psychological and musical development of children. When viewed from the form of poetry and melody, the song by SARIDJAH NIUNG BINTANG SOEDIBJO (IBU SOED) is suitable to be sung by the voice criteria of children aged 4-6 years.